2016
DOI: 10.1111/ans.13500
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic balloon dilatation of Crohn's strictures: a safe method to defer surgery in selective cases

Abstract: EBD is safe for both primary and post-surgical strictures. Stricture length and diameter of dilatation are predictive of success. In selected patients, treatment with EBD may reduce or delay the need for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Multiple predictors of treatment success were identified from the 60 endoscopic therapy studies. The most consistent predictor of treatment success was stricture length 22,47,48,52,58 . However, few studies included patients with strictures longer than 5 cm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple predictors of treatment success were identified from the 60 endoscopic therapy studies. The most consistent predictor of treatment success was stricture length 22,47,48,52,58 . However, few studies included patients with strictures longer than 5 cm.…”
Section: Resultsmentioning
confidence: 99%
“…Other medications explored in combination with EBD included antibiotics that were found to be linked with an increased likelihood of reintervention in one study 69 and concomitant corticosteroids that were associated with repeated intervention in two studies 47,58 …”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective study limited to small intestinal lesions, the rate of avoiding resection improved with dilation of 15 mm or greater in a univariate analysis 4 . Another retrospective study that included both small intestinal and colonic lesions reported improved outcomes with dilation of 12–15 mm or 5–8 greater. In a retrospective study including both small intestinal and colonic lesions using colonoscopy, no significant difference was found in procedure risk between diameters of 14–15 mm and 16–18 mm; however, the group that selected the dilation diameter of 16–18 mm had a longer dilation interval after the fourth dilation (mean 240 ± 136.7 days vs. 456 ± 357.3 days, P = 0.023) 7 …”
mentioning
confidence: 98%
“…The scope of the term “efficacy” is equally broad, ranging from avoiding surgery or the need for repeated EBD to the complete absence of recurrent abdominal symptoms caused by GI tract strictures. When measured by the rate of preventing the need for a repeated EBD (some overlap was detected), the long‐term efficacy rate is reported to be 46–93% 1–17 . The post‐EBD surgical conversion rate can be considered the most important long‐term efficacy indicator.…”
mentioning
confidence: 99%
See 1 more Smart Citation